Poynting vector analysis for wireless power transfer between magnetically coupled coils with different loads - Yunsheng Guo (Nature Portfolio, 2017)
Abstract Wireless power transfer is a nonradiative type of transmission that is performed in the near-field region. In this region, the electromagnetic fields that are produced by both the transmitting and receiving coils are evanescent fields, which should not transmit energy. This then raises the question of how the energy can be transferred. Here we describe a theoretical study of the two evanescent field distributions at different terminal loads. It is shown that the essential principle of wireless energy transfer is the superposition of the two evanescent fields, and the resulting superimposed field is mediated through the terminal load. If the terminal load is either capacitive or inductive, then the superimposed field cannot transfer the energy because its Poynting vector is zero; in contrast, if the load is resistive, energy can then be conveyed from the transmitting coil to the receiving coil. The simulation results for the magnetic field distributions and the time-domain current waveforms agree very well with the results of the theoretical analysis. This work thus provides a comprehensive understanding of the energy transfer mechanism involved in the magnetic resonant coupling system.